Organização do trabalho pedagógico para reinserção social do adolescente em conflito com a lei - Aguiar, Vagner Lima de (2024)
This dissertation is associated with the research line Culture, Educational Processes and Teacher Training, of the Stricto Sensu Postgraduate Program in Education at the State University of Western Paraná (UNIOESTE), Francisco Beltrão campus - PR. The research, which is part of the Educação Superior, Formação e Trabalho Docente (Higher Education, Training and Teaching Work - GESFORT– acronym in portuguese) research group, looks at the organization of pedagogical work in the Centro de Referência Especializado de Assistência Social (Specialized Social Assistance Reference Centre – CREAS – acronym in portuguese) for the social reintegration of adolescents in conflict with the law, analyzing public educational policies and their contradictions in this context. The relevance of the topic lies in the need to understand how pedagogical work can contribute to the re-socialization and guarantee of the rights of these adolescents, in a scenario marked by social inequalities and educational challenges. The general objective is to analyze the organization of pedagogical work at CREAS in Francisco Beltrão - PR, within the scope of public educational policies aimed at the social reintegration of adolescents in compliance with a socio-educational measure. The methodology adopted involves a qualitative approach, with quantitative support, including a bibliographical and documentary study and the application of a semi-structured questionnaire to CREAS socio educators. The theoretical-methodological basis allows us to understand education as a social and historical phenomenon, shaped by relations of production and the class struggle. The results point to the importance of education as an instrument of social transformation and the need for planned and intentional pedagogical work, in line with Historical-Critical Pedagogy. However, challenges such as school dropout and lack of interest in the educational practices offered to adolescents reveal the need to include a pedagogue in the team of socio-educators to implement the organization of pedagogical work, based on Historical-Critical Pedagogy. In the context of CREAS, this conception of education is fundamental to overcoming the contradictions between public policies and educational practice, by offering a method that allows social reality to be transformed through education, valuing social practice and the role of the educator as a mediator in engaging adolescents. The conclusion is that the effectiveness of socio-educational measures depends on the articulation between public educational policies, the organization of pedagogical work, and multidisciplinary work at CREAS, with a focus on building an inclusive and equal future for adolescents under socio-educational measures, by guaranteeing their right to education and social reintegration.